Transforming Islamic Education to Promote Religious Moderation and Prevent Radicalism - Afifatun, Siti; Ali, M. Makhrus; Isa, Khairunesa; Sajadah, Meilisa; Hariyati, Tri; Mulyani, Dessy Kurnia (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the transformation of Islamic education in promoting religious moderation and preventing radicalism in North Lampung, Indonesia. This study employed a qualitative descriptive approach using literature review and content analysis methods. Data were collected from academic journal articles, books, government policy documents, and previous studies related to Islamic education, religious moderation, multicultural education, and radicalism prevention. The collected data were analyzed systematically through data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that the transformation of Islamic education can be implemented through three strategic dimensions: strengthening a moderation-based curriculum, supervising extracurricular activities, and enhancing teachers' roles as agents of moderate Islamic values. The study also finds that integrating multicultural values, tolerance, social interaction, cooperation, and empathy into Islamic educational practices contributes significantly to preventing radical attitudes among students. In addition, the transformation of Islamic education in North Lampung demonstrates the importance of contextual and humanistic educational approaches in maintaining social cohesion within a plural society. This study contributes to the discourse of Islamic education by emphasizing the integration of religious moderation and multicultural awareness as preventive strategies against radicalism in local educational contexts. Therefore, strengthening moderate Islamic education is essential for fostering peaceful coexistence and sustainable social harmony in Indonesia.